A Separation Principle for Distributed Control - Rantzer, A. (Proceedings of the 45th IEEE Conference on Decision and Control, 2006)
A linear quadratic control problem is considered, where several different controllers act as a team, but with access to different measurements. The state feedback solution obtained in a previous paper is here extended to output feedback and a separation principle is proved. The condition that certain measurements are unavailable to some state estimators is enforced by imposing a requirement that the generated estimates must be insensitive to the changes in corresponding covariances between measurement noise and process noise